Analisis Layanan Callnak Centre Dalam Pengembangan Usaha Ternak Sapi Potong di Kota Parepare - Usman Usman; Andi Nuddin; Sahabuddin Toaha (Forum Agribisnis, 2021)
Beef Cattle is one of the meat-producing resources that have great benefits for the fulfilment and improvement of community nutrition. The low population of Beef Cows is because most of the livestock are kept on a small scale with limited land and capital. In addition, the weather does not threaten animal health. To carry out preventive activities against outbreaks of disease in livestock, the government program CallNak Center. The research objective was to analyze the effect of animal health services, health status checks, and artificial insemination on the development of Beef Cattle. The research method used quantitative research with a cross-sectional study approach. The research was conducted in Parepare City from August 2020 to April 2021. The sampling technique used non-probability sampling with purposive sampling with a total sample of 73 breeders. The data analysis used in this study is the Chi-Square Test. The results showed that the majority of respondents (76,71%) felt the benefits of animal health services, and health status checks and respondents considered beneficial were 78,08%. Meanwhile, respondents who felt the benefits of Artificial Insemination (IB) services were 50,68% or only a difference of 1,36% were considered less useful. Respondents who stated that they had experienced the development of beef cattle since the CallNak Center was 82,19%, while only 17,81% had ever developed. The results of the analysis show that animal health services and health status checks and those which significantly affect Artificial Insemination do not significantly affect the development of cattle in Parepare City.